Bis(quinoline-2-carboxylato-kappa 2 N,O)lead(II) - Mohammadnezhad, G.; Ghanbarpour, A.R.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The PbII atom in the title compound, [Pb(C(10)H(6)NO(2))(2)], is N,O-chelated by two quinoline-2-carboxylate anions in a distorted Psi-trigonal-bipyramidal environment; four atoms are connected to the PbII atom by regular coordination bonds. The structure also features two somewhat long Pb...O interactions [2.952 (3) and 3.014 (3) A]. These long interactions give rise to a layer coordination polymer having the lead atom in a distorted Psi-monocapped octahedral geometry.